Extirpation of the scholarly profession in pedagogy - ŚLIWERSKI, BOGUSŁAW (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Bogusław Śliwerski, Extirpation of the scholarly profession in pedagogy.Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 13-31.Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.25.01. In the article I am dealing with the issue of unscientific depreciation of pedagogy as a science, which manifests itself either in the lack of reliable scientific criticism of dissertations in this discipline or the escape of some educators into politics to implement their own social intervention projects. The dispute about the scientific nature of pedagogy arises from various research traditions, scientific schools, so the author presents several such methodological approaches, whose creators emphasize the criteria of scientificity and indicate the resulting limitations and their incomparability. Meanwhile, self-awareness of the academic criteria of pedagogy is important in the way of reviewing the scientific achievements of young academic staff. Based on reviews in post-habilitation proceedings, I present various types of arguments in favor of the unscientific status of someone’s research and the reaction of those whose publications are reviewed